COMPETITION AMONG YOUTUBERS; CELEBRITIES VS NON-CELEBRITIES - Lambok Hermanto Sihombing; Annisa Damayanti F.; Fadillah Zuriana; Puji Lestari (Program Studi Ilmu Komunikasi FISIP Universitas Sultan Ageng Tirtayasa, 2021)
This study is aimed to analyze and compare the effect of controversial celebrity YouTubers and non-celebrity YouTubers in Indonesia. In this study, researchers used three celebrity YouTubers and three non-celebrity YouTubers as a research object. There are several elements to be discussed in this study that include YouTube accounts, types of content, the number of subscribers, and viewers. The theoretical basis used in conducting the analysis is the theory of capital Pierre Bourdieu proposed by Tomasema. There are four capital forms; economic, human, social, and symbolic. Furthermore, the results of the research showed that the presence of celebrity YouTubers has an impact on the existence and careers of non-celebrity YouTuber.